2017
DOI: 10.1111/jfd.12618
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of exopolysaccharides from Arthrospira platensis against koi herpesvirus

Abstract: Although koi herpesvirus (KHV) has a history of causing severe economic losses in common carp and koi farms, there are still no treatments available on the market. Thus, the aim of this study was to test exopolysaccharides (EPS) for its antiviral activity against KHV, by monitoring inhibition and cytotoxic effects in common carp brain cells. These substances can be easily extracted from extracellular algae supernatant and were identified as groups of sulphated polysaccharides. In order to reach this aim, Arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…Recently it was discovered that extract from Clinacanthus nutans L. is active against CyHV-3 in experiments in vivo (12). Exopolysaccharide from Arthrospira platensis L. also indicated anti-CyHV-3 activity in experiments in vitro (18). In addition, our recent study proved that acyclovir inhibits CyHV-3 replication in experiments in vitro (24).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recently it was discovered that extract from Clinacanthus nutans L. is active against CyHV-3 in experiments in vivo (12). Exopolysaccharide from Arthrospira platensis L. also indicated anti-CyHV-3 activity in experiments in vitro (18). In addition, our recent study proved that acyclovir inhibits CyHV-3 replication in experiments in vitro (24).…”
Section: Discussionmentioning
confidence: 58%
“…Although ACV and T-ACV were not examined in the same experiment, a similar effect would have been expected because the antiviral activities of ACV and T-ACV against HSV-1 and HSV-2 were similar in a mammalian system (9,10). On the other hand, ganciclovir, another nucleoside analogue that differs from ACV by the presence of an additional CH2OH moiety, was also inactive against CyHV-3 virus (18). Based on these findings, it seems probable that there might be very narrow specificity of CyHV-3-encoded DNA polymerase for ACV-based molecules.…”
Section: Discussionmentioning
confidence: 91%
“…The anti‐CyHV‐3 activity of both nucleoside analogues was not described. Previously, Reichert, Bergmann, Hwang, Buchholz, and Lindenberger () demonstrated that another nucleoside analogue, ganciclovir (GCV), had no effect on CyHV‐3 replication in vitro. However, the GCV is different from the ACV because of the presence of an additional CH 2 OH moiety on the side chain (Marcier & Mertz, ).…”
Section: Discussionmentioning
confidence: 99%
“…This cyanobacterium contains a very potent naturally occurring antioxidant and free radical scavenging agents such as pigments (phycocyanin and Beta-carotene) [10] and polysaccharides [11], that are well-known products to protect against various diseases, such as renal failure [12], hypertension [13] and cancers [11,14]. Besides their antioxidant effects, pigments and polysaccharides of Spirulina platensis have been found to show antibacterial and antiviral activities [15,16].…”
Section: Introductionmentioning
confidence: 99%